The crises in the Middle East: reshaping the region’s geopolitical landscape and altering the global order - Seevan Saeed (Asian Review of Political Economy, 2025)
Abstract The recent events in the Middle East caught most political commentators, observers and thinkers by surprise. Who would have imagined that a non-state actor like Hamas could launch an attack on Israel and create such a complex condition for a powerful state, heavily supported by the USA and Western powers? However, crises in the Middle East often escalate unpredictably, defying calculations and expectations. This paper argues that since October 7th 2023, not only in the Middle East but also in several other regions worldwide, major rival powers have been struggling with crises that are leading to reshape the global order. The paper argues that the realms of Economy, Security, and Diplomacy among the primary global powers are all under scrutiny as they navigate the crises that have intensified significantly towards altering the global order.